Al-faskh al-qada'iy wa atsaruhu fi istimrar al-uqud: dirasah tahliliyah min khilal al-qanun al-madani al-urduni (Judicial annulment and its effects on the continuation of contracts: An analytical study through the jordanian civil law) - Hijrian A. Prihantoro (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
The purpose of this research is to investigate the issue of the continuation of the contract after judicial annulment through an analytical study within the Jordanian civil law. The contract contains a force binding on its sides by its respect. The contract also, for both parties, within the framework of the organization of relations governed by the law, can not be vetoed by one of the amendments, unless the agreement or the law so authorized. This basic principle in the theory of contract, which is called binding force, or the basis of the contract of the law of the deceased, according to this rule is that no one of the contracting parties can revoke the contract or modify its provisions individually, unless the law permits it or there is agreement between it And between the other. However, there are cases in which the law allows a contractor to reach a contract revocation despite the other party's right to contract in the binding contracts of the two sides to request the judge to award the contract if the other party fails to fulfill its obligation, with the discretion of the judge in this case. These cases are exceptions to the rule of contract of the law of contracting, which is the subject of our research.